Matematică
mariaaaaaaaaaaa
2021-04-14 21:31:00
1) ∫2-√5∫ - ∫√3+√5∫ + ∫1-√3∫= 2) ∫√3+√2∫ -∫√3+5∫ -∫1-√2∫ +∫-5∫= 3) ∫√2-√3∫ + ∫2-√3∫ =∫1-√2∫- ∫-3∫ = ∫-modul Va rog...
Răspunsuri la întrebare
malaipasha
2021-04-14 23:18:10

1 .    =  -  ( 2 - √5 )    - (√3 + √5)  + [ - ( 1 - √3) ]          =  - 2  + √5  - √3  - √5   - 1  + √3 = - 2  - 1 = - 3  2.        =  √3 + √2   - (√3 + 5 )  - [ - ( 1 - √2) ] + [ - ( - 5) ] =             = √3  + √2  -  √3  - 5  + 1  - √2 + 5 =  1  3.         =  - ( √2 - √3)  + ( 2 - √3)   +  [- ( 1 - √2) ] - [ - ( -3) ] =               = - √2  + √3  + 2 - √3  - 1   + √2   - 3 =  - 2 

mihaelapop2904
2021-04-14 23:19:25

1) I2-√5I-I√3+√5I+I1-√3I=-3 √3+√5≥0, atunci I√3+√5I=√3+√5 2-√5≤0, atunci I2-√5I=-(2-√5) 1-√3≤0, atunci I1-√3I=-(1-√3) Inlocuim: I2-√5I-(√3+√5)+I1-√3I= -(2-√5)-(√3+√5)+I1-√3I= -(2-√5)-(√3+√5)-(1-√3)= √5-2-(√3+√5)-(1-√3)= -2+√5-√3-√5+√3-1= -2-1+√5-√5-√3+√3=-3 2) I√3+√2I-I√3+5I-I√1-√2I+I-5I=1 I√3+√2I-(√3+5)-I1-√2I+I-5I= I√3+√2I-(√3+5)+1-√2+I-5I= √3+√2-(√3+5)+1-√2+I-5I= √3+√2-√3-5+1-√2+5= √3-√3+√2-√2-5+5+1=1 3) I√2-√3I+I2-√3I+I1-√2I-I-3I=-2 I√2-√3I+I2-√3I+I1-√2I-3= -(√2-√3)+I2-√3I+I1-√2I-3= -(√2-√3)+2-√3-(1-√2)-3= -√2+√3+2-√3-1+√2-3= -√2+√2+√3-√3+2-1-3=-2

Adăugați un răspuns